Effectiveness of Quantitative Research Methods Course Module in Fostering Students' Academic Literacy - Sriwati, Sriwati; Rochgiyanti, Rochgiyanti; Susanto, Heri; Prawitasari, Melisa (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
This research endeavors to implement pedagogical techniques aimed at enhancing students' writing prowess within the framework of learning modules for courses on quantitative research methodologies utilizing a feedback-oriented approach. This research was carried out employing a pre-experimental design, specifically the type one group pretest-posttest design. The experimental cohort comprised pupils enrolled in the Quantitative Research Methods course, belonging to the History Education Department at Lambung Mangkurat University during the odd semester of the academic year 2022/2023. The research outcomes indicate that implementing the quantitative research methods course module with a feedback approach substantially enhances students' academic literacy in composing research proposals. It can be asserted that the implementation of modules employing a feedback-oriented approach is efficacious in cultivating students' proficiency in academic literacy pertaining to quantitative research methodologies